Invictus - Eastwood, Clint, 1930-; Freeman, Morgan; Damon, Matt; Warner Bros. Pictures (United States : Warner Bros. Entertainment Inc., 2009)
He was imprisoned 27 years for his heroic fight against apartheid. So what does Nelson Mandela do after he is elected president of South Africa? He reject revenge, forgives his oppressors and finds hope of national unity in an unlikely place: the rugby field.
Based on the book'Playing the enemy' by John Carlin.
Special features: Matt Damon plays rugby: Turning a Hollywood Star into a Rugby Player ; Invictus music trailer.
Director of photography, Tom Stern ; production designed by James J. Murakami ; edited by Joel Cox, Gary D. Roach ; costumes designed by Deborah Hopper.
Morgan Freeman, Matt Damon.
LPF: U
DVD format, Widescreen (2.40:1), Dual-Layer format, suitable for all TV screens, Region 3, Dolby Digital.
Keywords: Mandela, Nelson, -- 1918-2013 -- Drama; Springboks (Rugby team) -- Drama; Presidents -- South Africa -- Drama; Nationalism and sports -- South Africa -- Drama; Sports films